Pelatihan Akuntansi Toko Trubus Karya Print untuk Meningkatkan Kualitas Laporan Keuangan Berbasis SAK EMKM: Pengabdian - Suryaningrum, Diah Hari; Munari, Munari (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The Financial Accounting Standards for Micro, Small, and Medium Enterprises (MSMEs) are one of the financial standards established to facilitate the preparation and presentation of simpler and more understandable financial reports for investors and creditors to provide financing assistance to MSME entrepreneurs. This condition occurred at the Trubus Karya Print Shop, a used printer service and trading business. This TKP Shop has been established for a long time and has adequate business activities, but has not been able to properly implement the EMKM SAK. This background is interesting to study related to the implementation of the EMKM SAK. This EMKM SAK consists of three components: the statement of financial position, the income statement, and notes to the financial statements. The results of observations during this community service showed that the financial system at the TKP Shop was recorded manually and was still very simple. The reason for making simple records was because the owner still did not understand how to prepare financial reports in accordance with standards and due to time constraints, so that preparing financial reports in accordance with the EMKM SAK has not yet been implemented. The results of the training and creation of this accounting system are expected to provide financial information for the TKP Shop owner.